Cognitive flexibility, growth mindset, transdisciplinary thinking, and resilience premises for an instructional innovation framework for design-based biology - Honra, Joelash R.
Addressing the longstanding concern of bridging theoretical learning with practical applications remains crucial in education. To tackle this challenge, educators must embrace innovative instructional approaches that integrate students’ real-world experiences. This study investigated the synergistic influence of Design-Based Biology Education (DBE) on students’ cognitive flexibility, growth mindset, and transdisciplinary thinking. Moreover, it examined how academic resilience moderates the effects of DBE on these outcome variables, alongside investigating whether transdisciplinary thinking predicts cognitive flexibility and growth mindset among biology students.